Hubungan Praktik Kesehatan pada Awal Kehidupan dengan Kejadian Stunting pada Balita - Rachmawati, Sutrani; Machmud, Putri Bungsu; Hatma, Ratna Djuwita (Media Kesehatan Masyarakat Indonesia, 2019)
Banten has the highest prevalence of stunting (29.6%) on Java island and has increased in the last three years. Health practice such as early initiation of breastfeeding, exclusive breastfeeding, complementary feeding, and vitamin A was important during child’s early life growth. This study analyzes the association between early life health practice and stunting among children aged 6-23 months in Banten 2017. This study used a cross-sectional design and used secondary data from PSG. The population in this study are the children aged 6-23 months who had become the sample of Banten Province PSG. Sampling used total sampling and selected 840 children who met the inclusion criteria. Analysis using chi-square test and multiple logistic regression. There were 25.36% of the child were stunting. There was no association between early life health practice and stunting (p=0.111) after controlled by child’s age, number of household, mother’s education and the interaction between health practice ane mother’s education. The interaction test showed that children who got inappropriate health practice and high mother’s education was 0.63 times become stunting (95% CI:0.36-1.11) and children who got appropriate health practice and low mother’s education was 1.82 times become stunting (95% CI:0.90-3.67). Health practice was not associated with stunting, but the interaction variables of health practice and mother’s education was associated.